How do EFL in-service teachers reflect on their critical incidents? The case of Iranian teachers. Issue 4 (4th July 2021) - Molani, Haideh; Yousefi, Mohammad Hosssein; Rostami, Farzad
ABSTRACT: The present study was conducted to explore and discuss different types of critical incidents that arise in Iranian EFL classes and how in-service EFL teachers reflected on their own critical incidents. 40 English teachers at different language institutes participated in the study. For the purpose of the data collection, reflective diaries, peer interactions, and in-depth interviews were conducted. Thematic analysis was utilized to analyze the data. After ensuring trustworthiness, different themes emerged: behavior, clashes, language proficiency, class participation, and individual differences . The results of the study have a number of implications for teacher education and can add to the existing literature on unpacking teachers' critical incidents.